Interplay between redox and protein homeostasis. Issue 2 (2nd April 2016) - Feleciano, Diogo R.; Arnsburg, Kristin; Kirstein, Janine
ABSTRACT: The subcellular compartments of eukaryotic cells are characterized by different redox environments. Whereas the cytosol, nucleus and mitochondria are more reducing, the endoplasmic reticulum represents a more oxidizing environment. As the redox level controls the formation of intra- and inter-molecular disulfide bonds, the folding of proteins is tightly linked to its environment. The proteostasis network of each compartment needs to be adapted to the compartmental redox properties. In addition to chaperones, also members of the thioredoxin superfamily can influence the folding of proteins by regulation of cysteine reduction/oxidation. This review will focus on thioredoxin superfamily members and chaperones of C. elegans, which play an important role at the interface between redox and protein homeostasis. Additionally, this review will highlight recent methodological developments on in vivo and in vitro assessment of the redox state and their application to provide insights into the high complexity of redox and proteostasis networks of C. elegans .